OP0031 A Phase 2 Study Evaluating the Efficacy and Safety of Subcutaneously Administered Ustekinumab and Guselkumab in Patients with Active Rheumatoid Arthritis Despite Treatment with Methotrexate. (9th June 2015) - Smolen, J.; Agarwal, S.K.; Ilivanova, E.; Xu, X.L.; Miao, Y.; Mudivarthy, S.; Xu, W.; Radziszewski, W.; Greenspan, A.; Beutler, A.; Baker, D.
Abstract : Objectives: To evaluate UST (anti-IL-12/23p40 mAb) and GUS (investigational anti-IL-23p19 mAb) in reducing signs and symptoms in active RA despite MTX. Methods: In this Ph2, randomized, double-blind, multicenter, PBO-controlled, parallel-group study, patients (18-80yrs) with active RA (≥6 tender joint count [TJC] and 6 swollen joint count [SJC] and serum CRP≥0.80mg/dL) despite MTX, were randomized to the following through wk28 (with MTX): PBO wks 0, 4, q8wks; UST90mg wks 0, 4, q8wks; UST90mg wks 0, 4, q12wks; GUS200mg wks 0, 4, q8wks; or GUS50mg wks 0, 4, q8wks. Patients were on MTX (10mg-25mg/wk) for ≥6 months with stable dose for a minimum of 12wks prior to randomization. Oral prednisone/equivalent (≤10 mg/day) and NSAIDs were permitted; previous and concomitant use of biologics not permitted. At wk16, PBO patients who failed to achieve ≥10% improvement (both TJC and SJC) received UST 90mg at wk16, 20, and 28. All patients were followed for safety through wk48. Primary endpoint was ACR20 response at wk28. Results: 274 patients were enrolled; 22 (8.0%) d/c through wk28. Major reasons for d/c: lack of efficacy (10 [3.6%]);AEs (8 [2.9%]). Patient demographics were generally similar between groups. Baseline clinical disease characteristic were well balanced across groups except median disease duration (slightly longer in PBO [6.3yrs] vs UST [4.15 yrs] and GUS [4.30 yrs] groups). Baseline median CRP for all patients was 1.5mg/dL and median SJC and TJC were 14 and 24, resp. Proportion of patents with ACR20 did not differ significantly between groups; however some differences were observed for secondary endpoints (Table ). Through wk48, 45.5% PBO, 50.4% combined UST, and 43.1% combined GUS had ≥1 treatment-emergent adverse events (TEAEs); serious TEAEs were reported in 5.5%, 6.4%, 2.8%, in PBO, combined UST and combined GUS, respectively. Death occurred in 1 patient (UST90mg q8wk) (suspected pulmonary embolism or thoracic aorta aneurysm). Infections were reported in 29.1%, 29.6%, and 22.9% in the PBO, combined UST, and combined GUS groups, respectively; serious infections occurred in 1 PBO patient (appendicitis), 1 UST 90mg q8wk-treated patient (UTI) and 2 GUS 200mg q8wk-treated patients (1 lobar pneumonia and 1 gastroenteritis). No TB, opportunistic infections, MI or stroke were reported. A serious TEAE of unstable angina was reported in PBO. There were 2 cases of malignancy: squamous cell carcinoma of lung in UST 90mg q12wk group and breast cancer in GUS 200mg q8wk. Conclusions: Neither UST nor GUS demonstrated significant efficacy in improving signs and symptoms of active RA based on ACR20 response at wk28. Improvements (based on nominal p<0.05) were observed in some secondary efficacy measures in both UST groups vs PBO. Both UST and GUS were generally well tolerated. Based on these results, inhibition of IL12 and/or IL23 does not appear to significantly alleviate signs and symptoms of active RA. These results provide additional insights into the differences between RA and psoriatic joint disease. Disclosure of Interest: J. Smolen Grant/research support from: Janssen Research & Development, LLC., S. Agarwal Grant/research support from: Janssen Research & Development, LLC., E. Ilivanova Grant/research support from: Janssen Research & Development, LLC., X. Xu Employee of: Janssen Research & Development, LLC., Y. Miao Employee of: Janssen Research & Development, LLC., S. Mudivarthy Employee of: Janssen Research & Development, LLC., W. Xu Employee of: Janssen Research & Development, LLC., W. Radziszewski Employee of: Janssen Research & Development, LLC., A. Greenspan Employee of: Janssen Scientific Affairs, LLC., A. Beutler Employee of: Janssen Research & Development, LLC., D. Baker Employee of: Janssen Research & Development, LLC.